Analisis Faktor Penyebab Keterlambatan Peserta Didik Tiba di Sekolah dalam Penerapan Karakter Disiplin - Hambali, Hambali; Martati, Badruli; Setiawan, Fajar; Habibullah, Habibullah (Jurnal Simki Pedagogia, 2026)
This study aims to describe the factors that cause the delay of students arriving at school in the application of discipline character. The research uses a descriptive qualitative approach with subjects consisting of principals, classroom teachers, and students in one of the elementary schools in Indonesia. Data collection techniques are carried out through direct observation of student arrival behavior, in-depth interviews with schools and students, and attendance documentation as supporting data. The results of the study show that students' tardiness is influenced by several main factors, namely low time management skills, lack of compliance with school rules, and lack of role and supervision from the family environment. Delays also occur repeatedly and show the weak internalization of disciplinary values in students. The implications of this study show the importance of a collaborative role between schools, parents, and students in shaping a culture of discipline, especially through positive habituation, setting examples, and strengthening rules that are educational and consistent. This research is expected to be the basis for schools to design strategies for fostering discipline character more effectively and sustainably.